2005
DOI: 10.1038/sj.onc.1209284
|View full text |Cite
|
Sign up to set email alerts
|

Repair and mutagenesis at oxidized DNA lesions in the developing brain of wild-type and Ogg1−/− mice

Abstract: OGG1 (8-oxoguanine DNA glycosylase-1) is one of the main DNA glycosylases present in mammalian cells. The enzyme removes 7,8-dihydro-8-oxoguanine (8-oxoG) lesions, believed to be the most important oxidized lesions due to their relatively high incidence and their miscoding properties. This study shows that in prenatal mice brains the repair capacity for 8-oxoG is 5-10-fold higher than in adult mice brains. Western blot analysis and repair activity in extracts from Ogg1 À/À mice revealed that OGG1 was responsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 49 publications
1
30
0
1
Order By: Relevance
“…In the present study, 8-oxoG repair activity was found to be approximately twofold higher in fetal tissues compared with those of adults, which is consistent with previous observations in both rat and mouse (Chen et al, 2002;Riis et al, 2002;Englander and Ma, 2006;Larsen et al, 2006). The complete lack of incision product observed in fetal tissues suggests that OGG1 is the sole contributor to 8-oxoG repair in GD 17 brain and liver nuclear extracts, and that the Nei-like DNA repair glycosylases (NEIL1/ 2/3), which have low in vitro repair capacity against 8-oxoG (Rosenquist et al, 2003), do not appear to contribute measurably to 8-oxoG removal in these gestational tissues during the fetal period of development.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the present study, 8-oxoG repair activity was found to be approximately twofold higher in fetal tissues compared with those of adults, which is consistent with previous observations in both rat and mouse (Chen et al, 2002;Riis et al, 2002;Englander and Ma, 2006;Larsen et al, 2006). The complete lack of incision product observed in fetal tissues suggests that OGG1 is the sole contributor to 8-oxoG repair in GD 17 brain and liver nuclear extracts, and that the Nei-like DNA repair glycosylases (NEIL1/ 2/3), which have low in vitro repair capacity against 8-oxoG (Rosenquist et al, 2003), do not appear to contribute measurably to 8-oxoG removal in these gestational tissues during the fetal period of development.…”
Section: Discussionsupporting
confidence: 81%
“…The importance of OGG1 in protecting the developing brain against oxidative insult is suggested by reports that expression and activity are highest in fetal rodent brain and decline with age (Chen et al, 2002;Englander and Ma, 2006;Larsen et al, 2006). We hypothesized that 8-oxoG is a developmentally pathogenic molecular lesion, and that ogg1 knock-out mice deficient in 8-oxoG repair will be more susceptible to increased oxidative DNA damage and neurodevelopmental deficits resulting from in utero exposure to enhanced formation of ROS, caused by fetal exposure to a single dose of METH (supplemental Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This was largely due to GC to TA transversions, believed to originate from 8-OHG mispairing with A during replication. Furthermore, rapid cell divisions seemed to be required for fixation of mutations, as a similar dose of radiation did not increase the mutation frequency, or the frequency of GC to TA transversions, in the adult brain [90]. [91] evaluated mitochondrial and nuclear incision activities of OGG1, UDG and the endonuclease III homologue (NTH1) in the caudate nucleus, frontal cortex, hippocampus, cerebellum and brain stem of 6-and 18-month-old male C57Bl/6 mice, observing a significant age-dependent decrease in incision activities of all three glycosylases in the mitochondria of all brain regions, whereas variable patterns of changes were seen in nuclei.…”
Section: Mutations and Polymorphisms In Dna Repair Genes And Risk Of Admentioning
confidence: 97%
“…For example, oxidative damage (from IR, UV, or chemical agents) induces base substitutions and single-base frameshifts and, notably, a preponderance of transversions (3,25,34,35,39), as observed with DHR cells (Table 1). This spectrum of oxidative damage-induced mutations is seen in cell and mouse models, is enhanced in the absence of the oxidative damage repair enzymes OGG1 and MTH1, is suppressed by antioxidants, and has been linked to tumorigenesis (3,25,34,35,39,46,58). The idea that UV-induced hypermutation results from oxidative DNA damage is further supported by the absence of a UV mutagenesis signature in the DHR/hypermutable cells (see Table S2 in the supplemental material).…”
Section: Discussionmentioning
confidence: 99%
“…This mutation spectrum, with a majority of mutants having compound point mutations, is significantly different from the non-DHR spectrum (P ϭ 0.045, Fisher's exact test). The mutation spectra (3,25,34,35,39). To determine whether DHRassociated hypermutation resulted from persistent oxidative stress, we examined the oxidation states of UV-C-irradiated DHR and non-DHR cells by using the fluorescent probe DHE (59).…”
Section: Uv-c Induces Delayed Hyperrecombinationmentioning
confidence: 99%